2011
DOI: 10.1029/2010jd014566
|View full text |Cite
|
Sign up to set email alerts
|

Submicron aerosol analysis and organic source apportionment in an urban atmosphere in Pearl River Delta of China using high-resolution aerosol mass spectrometry

Abstract: [1] The Pearl River Delta (PRD) region in South China is one of the most economically developed regions in China while also noted for its severe air pollution, especially in the urban environments. In order to understand in depth the aerosol chemistry and the emission sources in PRD, an Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) was deployed at an urban site in the Hong Kong-Shenzhen metropolitan area between 25 October and 2 December 2009. Ten minute-resolved measurement da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
139
6
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(184 citation statements)
references
References 61 publications
(153 reference statements)
37
139
6
2
Order By: Relevance
“…During the campaign, total nonrefractory PM 1 (NR-PM 1 ) as measured by the AMS ranged from 0.8 to 72.4 μg/m 3 with an average of 14.5 ± 9.7 μg/m 3 , which is within the upper range of measured concentrations in various other urban environments in the U.S. and Europe [Zhang et al, 2007b] but is significantly lower than what has been observed with AMS in other Chinese cities, e.g., Beijing, Shenzhen, and Kaiping [He et al, 2011;Huang et al, 2010Huang et al, , 2011b. On average, sulfate and organics combined amounted to 79.2% of nonrefractory fine particle mass (Figure 2a) with average concentrations of 7.9 ± 4.8 and 4.4 ± 3.6 μg/m 3 respectively.…”
Section: Overall Compositionmentioning
confidence: 84%
“…During the campaign, total nonrefractory PM 1 (NR-PM 1 ) as measured by the AMS ranged from 0.8 to 72.4 μg/m 3 with an average of 14.5 ± 9.7 μg/m 3 , which is within the upper range of measured concentrations in various other urban environments in the U.S. and Europe [Zhang et al, 2007b] but is significantly lower than what has been observed with AMS in other Chinese cities, e.g., Beijing, Shenzhen, and Kaiping [He et al, 2011;Huang et al, 2010Huang et al, , 2011b. On average, sulfate and organics combined amounted to 79.2% of nonrefractory fine particle mass (Figure 2a) with average concentrations of 7.9 ± 4.8 and 4.4 ± 3.6 μg/m 3 respectively.…”
Section: Overall Compositionmentioning
confidence: 84%
“…The exponential decreasing profile of aerosol vertical distribution is supported by aircraft measurement during PRIDE-PRD 2004 . The most recent analysis from high-resolution aerosol mass spectrometer (AMS) measurements (He et al, 2011) provides a similar mass concentration of ammonium sulfate to the value employed in this study. The mass and number concentration of ammonium sulfate over the sea are assumed to be half of the values over the continent.…”
Section: Design Of Numerical Simulationsmentioning
confidence: 89%
“…The OPOA time series is similar to that of nitrate, m/z 55 and m/z 60, suggesting that the aerosols were not aged but originated from different POA sources ( Figure S4). Earlier studies have also suggested that residual BBOA can accompany HOA in PMF analysis [He et al, 2011]. We speculate that OPOA is a mixture of both biomass burning and cooking aerosols.…”
Section: 1002/2014jd021978mentioning
confidence: 98%
“…BBOA-1 and BBOA-2 are correlated with m/z 60 (R 2 = 0.92 and 0.33, respectively) and m/z 73 (R 2 = 0.89 and 0.38, respectively). The contributions of residual BBOA, cooking, trash burning, and slightly oxidized SOA have been shown to be difficult to separate; thus, it is not surprising that a contribution from m/z 60, which increases the O:C ratio, is present in HOA [He et al, 2011;Aiken et al, 2009]. Elemental O:C ratios for different profile factors were obtained after fitting peaks in HR data analysis.…”
Section: 1002/2014jd021978mentioning
confidence: 99%